Corporate Governance and Corporate Performance: Effectiveness of Independent Directors in Technology-Based MESDAQ Listed Companies in Malaysia - Wong, Yah Yee (2009)
The Asian economic crisis and financial scandals have focused international attention on corporate failures and the case for strong corporate governance standards and practices to prevent them. This has brought the role of independent directors (IDs) into the spotlight and their role has emerged as a critical element for good corporate governance. This research seeks is to accomplish the objective to identify the factors that determine the effectiveness of IDs and their relationship with corporate performance. The unique background of companies in Malaysia, where majority of the companies are owned and controlled by founding families and MESDAQ listed companies, which are smaller in nature, provide clear justification and significance of this area of research. A theoretical framework based on the literature review was developed as the basis of the hypotheses development. The population for the study is comprised of 72 technology-based MESDAQ listed companies for the year 2008. Data were entered into an Excel spreadsheet before exporting into SPSS software for data analysis involving descriptive statistics and inferential statistics. Multiple regression analysis was carried out to test the hypotheses.The data analysis revealed that there is a high conformance to best practices in terms of proportion of IDs and CEO duality. However, there were concerns on the effectiveness of diversity and real independence. From the multiple regression analysis, we found no direct correlation between the identified variables and corporate performance. This does not necessarily mean that there were irrelevant. In fact, these variables were fundamental factors in determining the effectiveness of IDs. The major contribution of this research is the identification of the factors that promote the effectiveness of the IDs. A theoretical framework is developed to establish the link between the factors and corporate performance. In the case of smaller listed companies, it is evident that the factors do not have a direct link to corporate performance in the short run as shown in the findings. Therefore, if companies are looking for immediate improvements on corporate performance, focusing on these variables may not yield the intended results.